Benzene solubility in ionic liquids: working toward an understanding of liquid clathrate formation - Pereira, Jorge Fernando Brandão [UNESP]; Flores, Luis A.; Wang, Hui; Rogers, Robin D. (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2014)
The solubility of benzene in 15 imidazolium, pyrrolidinium, pyridinium, and piperidinium ionic liquids has been determined; the resulting, benzene-saturated ionic liquid solutions, also known as liquid clathrates, were examined with (1) H and (19) F nuclear magnetic resonance spectroscopy to try and understand the molecular interactions that control liquid clathrate formation. The results suggest that benzene interacts primarily with the cation of the ionic liquid, and that liquid clathrate formation (and benzene solubility) is controlled by the strength of the cation-anion interactions, that is, the stronger the cation-anion interaction, the lower the benzene solubility. Other factors that were determined to be important in the final amount of benzene in any given liquid clathrate phase included attractive interactions between the anion and benzene (when significant), and larger steric or free volume demands of the ions, both of which lead to greater benzene solubility.
Keywords: Aromatics; Benzene; Cation-anion strength; Clathrates; Ionic liquids